Plasma cell-free DNA as predictor of disease status in patients with differentiated thyroid cancer - a prospective study from a tertiary care institution - Goel, Rashi; Satapathy, Swayamjeet; Chandekar, Kunal Ramesh; Ballal, Sanjana; Agarwal, Shipra; Deo, Suryanarayan S. V.; Tripathi, Madhavi; Bal, Chandrasekhar (Frontiers in Oncology, 2024)
IntroductionPlasma cell-free DNA (cfDNA) estimation offers a non-invasive method to potentially diagnose, monitor, and prognosticate patients with malignancy. This prospective study aimed to assess plasma cfDNA levels in patients with differentiated thyroid cancer (DTC) to determine its role in predicting disease status in the post-operative setting.Materials and methodsThis was a single-center prospective observational study conducted at a public medical research university and hospital in New Delhi, India. 254 patients with DTC in the post-operative setting were included: 95 in Group 1 (active structural disease) and 159 in Group 2 (disease-free). Blood samples were collected for plasma separation and cfDNA extraction. The cfDNA concentrations were quantified and compared across various disease states.ResultsMedian values of plasma cfDNA (ng/µL) in groups 1 and 2 were found to be 0.272 (IQR: 0.137-0.442) and 0.222 (IQR: 0.123-0.398), respectively with no significant difference (p=0.122). cfDNA levels were significantly higher in patients in the age group ≥55 years (p=0.016). However, the cfDNA levels were not significantly associated with any of the other known prognostic markers of DTC.DiscussionBased on the results of this study, plasma cfDNA levels did not significantly predict disease status in patients with DTC in the post-operative setting.